Equivalent definition of some weighted Hardy spaces - Dilnyi, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We present the equivalent definition for spaces of functions analytic in the half-plane C_+ = {z: Re z > 0 } for which _|φ| < π2 {_0^+∞| f(r e^iφ)|^p e^-pσ r|φ| dr } < +∞.